Advances in quantum chemistry. - Sabin, John R.; Brandas, Erkki (Advances in quantum chemistry, 2003)
Advances in Quantum Chemistry presents surveys of current developments in this rapidly developing field that falls between the historically established areas of mathematics, physics, chemistry, and biology. With invited reviews written by leading international researchers, each presenting new results, it provides a single vehicle for following progress in this interdisciplinary area. - High quality and thorough reviews of various aspects of quantum chemistry.